The cbb(3)-type cytochrome oxidase assembly factor CcoG is a widely distributed cupric reductase - Marckmann, Dorian (Proc Natl Acad Sci U S A, 2019)
Copper (Cu)-containing proteins execute essential functions in prokaryotic and eukaryotic cells, but their biogenesis is challenged by high Cu toxicity and the preferential presence of Cu(II) under aerobic conditions, while Cu(I) is the preferred substrate for Cu chaperones and Cu-transport proteins. These proteins form a coordinated network that prevents Cu accumulation, which would lead to toxic effects such as Fenton-like reactions and mismetalation of other metalloproteins. Simultaneously, Cu-transport proteins and Cu chaperones sustain Cu(I) supply for cuproprotein biogenesis and are therefore essential for the biogenesis of Cu-containing proteins. In eukaryotes, Cu(I) is supplied for import and trafficking by cell-surface exposed metalloreductases, but specific cupric reductases have not been identified in bacteria. It was generally assumed that the reducing environment of the bacterial cytoplasm would suffice to provide sufficient Cu(I) for detoxification and cuproprotein synthesis. Here, we identify the proposed cbb(3)-type cytochrome c oxidase (cbb(3)-Cox) assembly factor CcoG as a cupric reductase that binds Cu via conserved cysteine motifs and contains 2 low-potential [4Fe-4S] clusters required for Cu(II) reduction. Deletion of ccoG or mutation of the cysteine residues results in defective cbb(3)-Cox assembly and Cu sensitivity. Furthermore, anaerobically purified CcoG catalyzes Cu(II) but not Fe(III) reduction in vitro using an artificial electron donor. Thus, CcoG is a bacterial cupric reductase and a founding member of a widespread class of enzymes that generate Cu(I) in the bacterial cytosol by using [4Fe-4S] clusters.